Prevalence of Palatogingival Grooves in a Libyan Population and Their Relationship with Periodontal Diseases - Radhakrishnan, Rohit; Deshpande, Neeraj; Kasim, Suad A (Journal of Orofacial Research, 2012)
Aim: The aim of the present study was to evaluate the prevalence of palatogingival grooves and its correlation to the periodontal health in maxillary incisors. Materials and methods: The 200 individuals, aged between 18 and 60 years, were examined for the presence of the palatogingival grooves in the four maxillary incisor teeth. Plaque index (PLI), gingival index (GI) and periodontal disease index (PDI) were used to evaluate the health of the periodontal tissues on the lingual surfaces of the maxillary incisor teeth. Results: The prevalence of palatogingival grooves in the study sample was 7.5% with no significant gender difference. The lateral incisors had the greatest prevalence of palatogingival grooves (1.68%). There were significant differences in periodontal health between teeth with and without palatogingival grooves. Conclusion: This study shows significant association between palatogingival grooves and periodontal disease.